Orquiepididimite causada por Corynebacterium sp e Proteus mirabilis em cordeiro da raça Lacaune: relato de caso - Dalanezi, Felipe Morales [UNESP]; Silva, Luis Fernando Mercês Chaves [UNESP]; Oliveira, Sidnei Nunes de [UNESP]; Araujo, Endrigo Adonis Braga de [UNESP]; Zahn, Fabíola Soares [UNESP]; Prestes, Nereu Carlos [UNESP]; Santis, Giovana Wingeter Di [UNESP] (My University, 2015)
Orchiepididymitis is the inflammation of both, testis and epididymis and may be caused by microbial agents such as Brucella ovis. Thus, the aim of the present report is to present a case of orchiepididymitis in a Lacaune ram with unilateral testicular enlargement. Ultrasonography of the testis revealed the presence of a circular hypoechogenic structure adjacent to the testicular parenchyma. Corynebacterium sp was isolated from the surgically removed testis. Two months after removal of the affected testis, the animal returned to the Veterinary Hospital due to an enlargement of the remaining testis. A new ultrasonographic exam revealed the presence of abscesses in the testicular parenchyma and periorchitis. After orchiectomy, Proteus mirabilis was isolated from the material.

A orquiepididimite é uma inflamação do testículo e epidídimo e pode ser causada por agentes microbianos tal como Brucella ovis. Desta maneira, a presente descrição teve por objetivo relatar orquiepididimite em um carneiro da raça Lacaune apresentando aumento testicular unilateral. O exame ultrassonográfico dos testículos revelou uma estrutura hipoecóica circular adjacente ao parênquima testicular. Através do cultivo microbiano do testículo retirado cirurgicamente, a bactéria Corynebacterium sp foi identificada como agente causador do quadro. Ao retornar para um novo atendimento no hospital veterinário, cerca de dois meses após o primeiro atendimento e retirada do testículo afetado, o animal apresentava aumento do testículo remanescente. Novamente foi realizado exame ultrassonográfico no qual foram observados abscessos no parênquima testicular e periorquite. Procedeu-se a orquiectomia e após exame microbiológico, a bactéria Proteus mirabilis foi isolada.
Orchiepididymitis caused by corynebacterium SP. and proteus mirabilis in the Lacaune ram: a case report
Keywords: Ovine; Testis; Bacterial infection; Infeção bacteriana; Ovino; Testículo